Digital Transformation Strategy in Islamic Microfinance Cooperatives: A Case Study of Bmt Ugt Nusantara's Innovation - Mansyur, Abdussalam; Suyoso Putra, Yuniarti Hidayah (Greenation Research & Yayasan Global Resarch National, 2024)
This study examines the implementation of digital transformation strategy at KSPPS BMT UGT Nusantara, which operates 298 service offices across Indonesia. The research aims to analyze the development and implementation process of digital transformation strategy in improving operational efficiency while maintaining Shariah compliance. Employing a qualitative approach with a single case study method, this research integrates Digital Transformation Theory, Technology Acceptance Model, and Institutional Theory as its analytical framework. Data were collected through in-depth interviews with 20 key informants, direct observations, and document analysis during September-December 2024. The findings reveal that successful digital transformation in BMT requires a holistic approach integrating technological aspects, Shariah compliance, and social empowerment. The implementation of digital transformation has resulted in a 45% increase in operational efficiency, 78% growth in digital financing portfolio, and expanded service coverage to underserved areas. This research contributes to the development of a digital transformation model that integrates Islamic values and provides practical recommendations for implementing digital technology in Islamic microfinance institutions.